Islam in Russia: Historical Facts and Modern Developments - Akhmetova, Elmira (IAIS Malaysia, 2013)
Two decades have passed since the lifting of the ‘Iron Curtain’, an ideological boundary erected by the Soviet Union to seal itself off from the rest of the world from 1945 to 1990. Yet, the subject of Islam in Russia and especially the history of Islam on Russian soil continues to be one of the less studied topics in international scholarship. Accordingly, the present work is a response to the existing information and literature deficiency on the subject of Islam in Russia. It gives a brief introduction to Islam in contemporary Russia.